DESIGN OF EBB AND FLOW AUTOMATIC HYDROPONIC SYSTEM FOR CHILLI PEPPER CULTIVATION - Delya, Buti (The University of Lampung, 2014)
Ebb and flowhydroponic systemgenerally used a timer to controlnutrient addition. The use of the timer, howeverhas major disadvantage including inefficiency of nutrient usage. This research aimed at designing of ebb andflow automatic hydroponic system which able to turn on/off the pump based on the moisture content usingmicrocontroller.The research was conducted at Greenhouse Facility of the Integrated Field Lab of AgricultureSchool, the University of Lampung from April - June 2014. The procedure begins with the manufacture ofinstrument, calibration, system design tool, the power supply circuit, equipment test and field test. The resultsshowed that has been successfully realized automatic ebb and flow hydroponic system working based on themoisture content. The value of setting point obtained for controling water content for turning on the pump was< 34.95%andturning off the pumpwas > 69.83%. Cultivation testusingchilli pepper resulted thatautomatic ebband flowhydroponic systemwas significally better thanmanually systemone, interms of plantheight and numberof leaves.